Phylogenetic Aspects of Antibiotic Resistance and Biofilm Formation of P. aeruginosa Isolated from Clinical Samples - Maryam Motevasel; Masoud Haghkhah; Negar Azimzadeh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Biofilm production and drug resistance phenomenon play a critical role in P. aeruginosa infections. Several genes, including psl, pel, brlR, and mex, are involved in the phenomenon. The aim of this study was to find the relationship between the mentioned genes and the sources of P. aeruginosa infections. Materials and Methods. Fifty-nine P. aeruginosa isolates detected from clinical specimens were used to determine antibiotic susceptibility patterns, prevalence of the genes using PCR, biofilm formation, biofilm eradication concentration assay (MBEC), and epidemiological characteristics using pulsed-field gel electrophoresis (PFGE). Results. The results showed that 35.6% and 16.94% of all the samples were isolated from urine and wounds, 81.33% of the isolates were biofilm producers, 27.11% were multidrug-resistant (MDR), and 100% of the main biofilm former genes belonged to pslA. 94.91% of the isolates possessed brlR and mexA, and 91.5% of them expressed pslA. It was also indicated that neither ciprofloxacin nor imipenem could eradicate the formed biofilms. Moreover, we could identify 81.4% distinctive restriction profiles among the isolates, using an 80% similarity cutoff point; brlR and pel genes were significantly (P=0.032; P=0.044) related to phylogenetic pulsotypes. Comparison of the dendrogram in the isolates revealed that the detected isolates from urine were present in 12 different pulsotypes. Conclusion. It was found that there was a relationship between MDR, biofilm production, and brlR and pel genes among the isolates. It is distinguished there were similar genetic patterns between detected isolates from urine and could be concluded that the urinary tract played a critical role in maintaining and transferring biofilm drug-resistant genes of P. aeruginosa in clinical sites. The study highlights the importance of urine in distribution of clinical biofilm formation and drug-resistant P. aeruginosa isolates.